1990
DOI: 10.1136/jnnp.53.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of regional cerebral blood flow and cognitive performance in Alzheimer's disease.

Abstract: Single photon emission computed tomography (SPECT) with 99mTc-HMPAO was used to image 26 patients with dementia of the Alzheimer type (DAT) and 10 healthy controls. Regional cerebral blood flow (rCBF) data indicated a relative sparing of the occipital regions in DAT. Normalisation to occipital flow illustrated highly significant CBF deficits in a number of cortical regions, particularly in the left and right posterior-temporal cortex in DAT compared to controls. The cognitive performance of DAT patients was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
79
0
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(88 citation statements)
references
References 21 publications
8
79
0
1
Order By: Relevance
“…In Alzheimer's disease (AD) the measurement of re gional cerebral blood flow (rCBF) by single-photon emis sion computed tomography (SPECT) reveals a decreased relative cortical perfusion which is typically predominant in temporal and parietal cortex [1,2], This pattern matches the metabolic abnormalities which can be dem onstrated in AD patients by the more sensitive method of positron emission computed tomography [3][4][5], The re gion-specific reductions in CBF determined by SPECT are associated with latcralizcd cognitive functions such as language and praxis [6][7][8]. The ability of rCBF measure ment by SPECT to reflect in vivo the typical topography of morphological changes in AD seen at neuropathological examination [9] is a valuable aid in the early recogni tion of AD and in its differentiation from other dement ing disorders.…”
Section: Introductionmentioning
confidence: 99%
“…In Alzheimer's disease (AD) the measurement of re gional cerebral blood flow (rCBF) by single-photon emis sion computed tomography (SPECT) reveals a decreased relative cortical perfusion which is typically predominant in temporal and parietal cortex [1,2], This pattern matches the metabolic abnormalities which can be dem onstrated in AD patients by the more sensitive method of positron emission computed tomography [3][4][5], The re gion-specific reductions in CBF determined by SPECT are associated with latcralizcd cognitive functions such as language and praxis [6][7][8]. The ability of rCBF measure ment by SPECT to reflect in vivo the typical topography of morphological changes in AD seen at neuropathological examination [9] is a valuable aid in the early recogni tion of AD and in its differentiation from other dement ing disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The growing literature concerning cerebral blood flow (CBF) in Alzheimer's disease (AD) raises new issues regarding CBF decline which is typical of the disease [1][2][3][4][5][6][7][8][9][10][11]. Mechanisms of decline of CBF in AD are still under debate, some authors arguing for a decrease in cerebral metabolic demands as the principal cause [12], others proposing a decline in CBF due to age-related accumulations of the deleterious effects of various disease processes affecting the blood supply of the brain and secondarily reducing its metabolism [13][14][15].…”
mentioning
confidence: 99%
“…Although recently criticized [ 17] for the long interval necessary' to complete the scintigraphic examination, we did not find a high refu sal rate by the patients. A further ratio was obtained in accordance to that previously described [9].…”
Section: Methodsmentioning
confidence: 63%
“…For many years one of the more promising agents for Accepted: April 3. 1993 demonstrating regional cerebral blood flow were the l23I-labeld amine derivatives and in the past two years the " mTcHM-PAO [10][11][12][13][14], Furthermore SPECT has proved to be potentially useful in detecting AD by demonstrating patterns of reduced cerebral blood flow in temporoparie tal association cortex [13,[15][16][17] comparable to those obtained with a more sophisticated procedure, such as positron emission tomography (PET) [ 18,19], Returning to the main question of this report, the rela tionship of age at onset of AD and its clinical severity, Jagust et al [9] reported a relative left frontal hypoperfu sion in presenile but not in senile-onset patients using SPECT imaging. They concluded that available data pro vide evidence for an involvement of left-frontal hemi sphere in patients with early onset Alzheimer's disease.…”
mentioning
confidence: 99%